Unsur-Unsur Fantasi dalam Motif Novel Franskenstein Karya Marry Shelly - Fransisca Dwi Harjanti (sarasvati, 2019)
This writing study of novels which contain elements of fantasy. Data taken from a novel titled frankenstein the work of marry shelly. That has been a problem in writing this is fantasy elements that was found in a motive. The purpose of this writing is described the fantasy elements that was found in a motive a novel franskenstein shelly marry work. Data collection techniques use the technique of documentation. The result of for the assessment of novels states that there are several motives that was found in the novel. Namely the motives have good enough fantasy elements, oddity as well as something that was felt to be does not make sense that was found in the motives. Motives which contain elements of fantasy of them the success of created man, pursued shadow fear, the sinister which is thirsty creature is knowledge, the sinister which is benevolent creature, the wickedness of human beings, heartache and revenge, the creation of the new man. In that they exist motives fantasy elements commit the morbidly artist footage, oddity, as well as something that does not make sense.